Spatial dimension of poverty in rural Nigeria (2010)
Poverty is a rural phenomenon in Nigeria. This study investigated poverty profile across geopolitical zones in rural Nigeria, using the 2003/2004 NLSS data. The result of FGT poverty decomposition shows that majority of the poor (84%) live in the rural area. Northwest zone had the highest relative contribution to incidence and depth of national rural poverty (29 and 30% respectively) while Southwest had the least relative contribution (4 and 3% respectively). Although North-central had the highest level of severity of rural poverty (P2 = 0.1454), North-west accounted for the highest relative contribution (30%) to national rural poverty.